The matter of absence. (October 2013) - Frers, Lars
In recent writings the concept of absence has been used to question the reach of phenomenological accounts of the human-world relation from a deconstructionist perspective. This article argues that absence is rooted in the corporeal embeddedness of human beings in the world that surrounds them. This is the case although absences refer to entities that are not present. Discussing the absence-presence relation, it is made clear that the simultaneity of absence and presence is not paradoxical, because the absence of presence and the presence of absence refer to different entities. Contrary to the connotation of absence with Derrida, the spectral and hauntings, absences are experienced in a wide variety of practices that are both extraordinary and mundane. A detailed investigation into the processes in which absences are experienced then shows how an experience of absence comes into being and what affects the power of the experience. The article argues that the experience of absence is stronger when it refers to practices, emotions and corporal attachments that have been deeply ingrained into those who experience the absence. Since materiality, embodiment and (the lack of) resistance play a crucial role in the actual experience of absences, the conceptualization of absence should reflect these qualities. It is precisely because absence is rooted in processual corporality that absence can unfold such disturbing power. Those who experience something as absent have to fill the void that they experience with their own emotions, they have to bridge the emptiness that threatens their established expectations and practices. Accordingly, absence is presented as a phenomenologically grounded concept that gains its epistemological and experiential quality through its connection to the corporal body, its senses and emotions, and the world around it.